In Pursuit of Social Justice: Emic and Etic Perspectives of Social Service Providers. Issue 3 (2nd October 2017) - Weng, Suzie S.; Clark, Paul G.
ABSTRACT: Professional social service providers have an obligation to seek social justice for their clients and the communities they serve. Using a case-study approach, this exploratory qualitative study examined how providers address community needs from emic and etic perspectives and the influence of race concordance on the development of these perspectives in relation to social justice. Themes found include: (a) understanding the community, (b) providing culturally appropriate services, and (c) fighting for social justice. Suggestions are offered for narrowing the gap between social justice knowledge and action taking. Suggestions are also offered for providing more culturally appropriate social services.